IMPROVING TEACHERS' SKILLS IN ACTIVE, CREATIVE, EFFECTIVE, AND FUN (PAKEM) LEARNING THROUGH TRAINING AND GUIDANCE ACTIVITIES (LATBIM) - Siti Hadijah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine the effectiveness of efforts to improve teachers’ skills in implementing PAKEM through LATBIM at SD Negeri 158 Pekanbaru. Meanwhile, the purpose of this school action research activity is generally to improve the quality of the process and learning outcomes at SD Negeri 158 Pekanbaru. The results of the study were seen from the result of the research in cycle 1, obtaining the average score of the pretest of 6.18 or about 62%, while the average score of the posttest increased to 9.06 or 91%. Data from the observation showed that the students’ activity reached 6.23 (fair) in Civics, 6.31 (fair) in PAI, and 6.45 (fair, close to good) in Arts. Thus, the hypothesis stating "if the Training and Guidance (LATBIM) in the Active, Creative, Effective, and Fun Learning (PAKEM) was implemented properly, the teachers’ skills in implementing PAKEM at SD Negeri 158 Pekanbaru increased" was accepted.